حرمان الذكور من الميراث بين الشرع والأعراف الاجتماعية: مجتمع المننجكابَو في سومطرة الغربية أنموذجاً: Depriving Males of Inheritance between Sharia and Social Custom: The Minang Kabau Community in West Sumatra as a Model - Majid, Muamar Maruf Azizman; Elatrash, Radwan Jamal; Shkokani, Najwa Naief (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص يهدف هذا البحث إلى دراسة عُرف مجتمع المننجكابو في سومطرة الغربية في مسألة توزيع الحقوق المالية، وبيان موقف الشرع من توزيعها حسب العادات والأعراف الاجتماعية. والغريب أن هذا المجتمع السومطري له عادات فريدة من نوعها إذ أنه يخصص تقسيم الحقوق ليدور بين الإناث مطلقًا ويحرم الذكور. ذلك أن المنتشر بين المسلمين أن الذكور يحرمان الإناث من حقهن في الميراث، أما أن يحرم الذكور من الميراث فهذا ما لم نكن نتوقعه. وقد اعتمد البحث على المنهج الاستقرائي لاستقراء ودراسة نظام الميراث في الإسلام حسب ما ورد في القرآن الكريم والسنة النبوية، وكذلك لدى عُرف مجتمع المننجكابو في سومطرة الغربية من خلال الرجوع إلى كتابات العلماء المتخصصين في ذلك وتفاسيرهم، كما أنه يعتمد على المنهج التحليلي عن طريق تحليل موقف الشرع لهذا التطبيق. وتوصلت الدراسة إلى عدة نتائج، من أهمها: أن المجتمع المننجكابَو التزم بنظام أمومي معين؛ فالأولاد والأحفاد يحملون نسبهم إلى الأم في الحياة الاجتماعية مع مراعاة التوثيق الجينيولوجي (Genetik) والشرعي لآبائهم. من جهة أخرى، فإن نظام الميراث لدى عُرف المجتمع المننجكابَو نوعان: الأول: الميراث العالي؛ وهذا النوع من الميراث لا يتعارض مع الشريعة الإسلامية، بل له أساسٌ في الدين، لأن حقيقة هذا الميراث بمنزلة الوقف. والنوع الثاني: الميراث المنخفض؛ وهذا النوع لا خلاف بين علماء الإسلام فيه لأن توزيعه التزم بأحكام الميراث الشرعي الإسلامي. Abstract This research aims to study the custom of the Mingkabau community in West Sumatra in the matter of distributing financial rights, and to clarify the position of Sharia concerning their circulation comparable to social traditions and norms. Astonishingly enough, this Sumatran society has unique habits in that it allocates the division of rights to take place among females absolutely and excludes males. That is because it is common among Muslims that males deprive females of their right to inherit, but that males are deprived of inheritance, this is what we did not expect. The research relied on the inductive approach to extrapolate and study the inheritance system in Islam according to what was mentioned in the Holy Qur’an and the Sunnah of the Prophet, as well as the custom of the Mingkabau community in West Sumatra by referring to the writings of scholars specialized in that and their interpretations, and it relies on the analytical method by analyzing the position of Sharia for this application. The study reached several results, the most important of which are: that the Mingkabo community adhered to a certain matriarchal system; Children and grandchildren carry their lineage to the mother in social life, considering the genetic and legal documentation of their fathers. On the other hand, the system of inheritance according to the custom of the Mingkabo society is of two types: the first: high inheritance; This type of inheritance does not contradict Islamic law, but rather has a basis in religion, because the reality of this inheritance is like a waqf. The second type: low inheritance; There is no disagreement among Islamic scholars regarding this type, because its distribution adheres to the provisions of Islamic legal inheritance.